Professional and moral responsibilities of notaries in supporting development in Medan City. Issue 1 (April 2020) - Natasari, E; Ginting, B; Sitepu, R; Kalo, S
Abstract: Medan is the third largest city in Indonesia, which has a fast growing city with massive property development such as flats and apartments. In addition to making the development by the prevailing laws and regulations. It must also consider spatial planning and the environmental aspect. Notaries, as public officials authorized to do the authentic deeds, are required to take both legal and moral responsibility for deeds they make. This normative legal research aims at describing the role of the notary as an official in doing authentic deeds associated with the construction of residential apartments in Medan. The results show that there are several problematic apartment buildings in Medan. These exist even though the notary involved from the process of doing a deed to ensure the ownership of the land and building permit to the availability of infrastructure, facilities, and public utilities. As a general official deed maker, a notary must be able to be legally and morally responsible and ready to accept any criminal consequences. Therefore, through the Indonesian Notary Association (INA), notaries must be coached gradually by the notary supervisory board with knowledge and skill in doing authentic deeds and must also be optimally monitored in carrying out their duties and responsibilities as public officials.